Traditional Foods General and Consumer Aspects - Kristbergsson, Kristberg; Oliveira, Jorge (Integrating Food Science and Engineering Knowledge Into the Food Chain, 2016)
This first volume of the Trilogy of Traditional Foods, part of the ISEKI Food Series, covers general and consumer aspects of traditional foods. It offers numerous recipes of traditional foods from across the world, with some chapters providing detailed descriptions on how to mix, cook, bake or store a particular food item in order to produce the desired effect. Traditional Foods; General and Consumer Aspects is divided into six sections. The first section focuses on general aspects of traditional foods and covers the perception of traditional foods and some general descriptions of traditional foods in different countries. This is followed by sections on Traditional Dairy Products, Traditional Cereal Based Products, Traditional Meat and Fish Products, Traditional Beverages and Traditional Deserts, Side Dishes and Oil products from various countries. The international List of Contributors, which includes authors from China, Bulgaria, Portugal, France, Norway, Romania, Slovakia, and Brazil, to name a few, shows its truly international perspective. The volume caters to the practicing food professional as well as the interested reader.